The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1136/fg.2009.000430
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of screen based simulators in the training and assessment of colonoscopists

Abstract: Incorporation of screen based simulators into medical training has recently gained momentum, as advances in technology have coincided with a government led drive to increase the use of medical simulation training to improve patient safety with progressive reductions in working hours available for junior doctors to train. High fidelity screen based simulators hold great appeal for endoscopy training. Potentially, their incorporation into endoscopy training curricula could enhance speed of acquisition of skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several studies showed that the use of VR in training programs improves skill acquisition amongst patients, trainers, and trainees. Maximum benefit has been seen amongst novice trainees [3]. Some reviews tried to determine the role of VR simulation within modern educational programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that the use of VR in training programs improves skill acquisition amongst patients, trainers, and trainees. Maximum benefit has been seen amongst novice trainees [3]. Some reviews tried to determine the role of VR simulation within modern educational programs.…”
Section: Discussionmentioning
confidence: 99%
“…There are some published trials that tested the validity of VR training simulation. Thereby, VR has shown potential to improve existing trainings in endoscopy and laparoscopic training programs [3,4]. Additionally, studies showed that the learning effect is higher when we actively do things rather than only read, watch, or listen to them [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that individuals who require high volume experiential learning (frequently required at the initial stages of skills acquisition) will be required to spend time on models and simulators before exposure to patients. This will be necessary for basic skills acquisition4 5 as well as more advanced techniques.…”
Section: Endoscopy Training: the Futurementioning
confidence: 99%
“…Procedure-based assessment and direct observation of procedural skills are currently used to validate practical competencies and can be useful learning and feedback tools but are rather crude and not entirely objective.VR simulation is a validated assessment for surgical training 1 and has been shown to be transferable to the operating theatre. 2 Since a structured and supervised training programme on simulators is required for learning to occur, 3 validated qualification of technical skills can help to ensure that surgeons perform to an acceptable standard and in doing so can demonstrate public, political and professional accountability for safe and effective training. Number of movements of right instrument <2,500…”
mentioning
confidence: 99%